2018
DOI: 10.4172/2368-0512.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosuvastatin on serum levels of vaspin and visfatin in patients with CAD

Abstract: METHODS: 80 patients who underwent coronary angiography due to symptoms of stable angina were enrolled in the study. 40 patients received Rosuvastatin 20 mg/day was compared to another 40 patients, as a control group, who refused statin treatment and preferred lifestyle modifications intervention. Main outcome measure: Clinical parameters, lipid profile, troponin I, high-sensitivity C-reactive protein (hs-CRP), Vaspin and Visfatin levels were assayed at the beginning and after 3 months. CAD severity was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Also, the present study found a significant positive correlation between vaspin and D-dimer levels in all groups. Experiments also indicated that vaspin could inhibit the release of many inflammatory markers in vascular smooth muscle cells and reduce FFA-induced apoptosis in endothelial cells [39].…”
Section: Discussionmentioning
confidence: 97%
“…Also, the present study found a significant positive correlation between vaspin and D-dimer levels in all groups. Experiments also indicated that vaspin could inhibit the release of many inflammatory markers in vascular smooth muscle cells and reduce FFA-induced apoptosis in endothelial cells [39].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that administration of atorvastatin, a lipophilic statin, decreases visfatin serum levels in Type II diabetic patients (Kadoglou et al 2012). In humans, serum visfatin levels have been decreased with the treatment of rosuvastatin in diabetic patients (Werida et al 2018). Both pravastatin and rosuvastatin decreased the visfatin level, but only pravastatin improved the fasting glucose level and body weight in our study.…”
Section: Discussionmentioning
confidence: 99%